Executive dysfunction and risk of suicide in older adults: a population-based prospective cohort study. Issue 5 (9th February 2021) - Oh, Dae Jong; Han, Ji Won; Bae, Jong Bin; Kim, Tae Hui; Kwak, Kyung Phil; Kim, Bong Jo; Kim, Shin Gyeom; Kim, Jeong Lan; Moon, Seok Woo; Park, Joon Hyuk; Ryu, Seung-Ho; Youn, Jong Chul; et al.
Abstract : Objective: It is uncertain what factors increases the risk of suicide in older adults without depression, and it is unknown whether executive dysfunction (ED) is one of those factors. We aimed to examine the effect of ED on the risk of suicide in non-demented older adults without depression. Methods: In an ongoing population-based prospective cohort of Korean older adults, we identified suicide using the National Mortality Database and suicidal ideation or attempt (SIA) based on the Korean version of the Mini International Neuropsychiatric Interview. We defined ED as performing below −1.5 SD of age-adjusted, gender-adjusted and education-adjusted norms in any of following tests: Frontal Assessment Battery, Trail Making Test A, Digit Span Test or Verbal Fluency Test. Results: The mean age of the 4791 participants at baseline was 69.7 (SD 6.4) years, and 57.1% of them were women (mean follow-up duration=4.9 years). ED at baseline increased the risk of suicide by about seven times (HR 7.20, 95% CI 1.84 to 28.12, p=0.005) but did not change the risk of SIA. However, cognitive impairment without ED did not change the risks of suicide and SIA. In participants with ED, being aged 75 years or above, living alone, and having a low socioeconomic status were associated with the risk of suicide. Conclusion: ED is a strong risk factor of late life suicide independent from depression, particularly in very old adults living in disadvantaged environments.